Nipah virus as an emerging threat: mutational dynamics, pathogenesis, and advances in vaccine development- a systematic review - Sadia Afrin; Md. Rezwan Ahmed Mahedi; Asma Akhter Radia; Joti Devi (Intelektual Pustaka Media Utama, 2026)
Nipah virus (NiV) is an emerging zoonotic pathogen with significant pandemic potential. Large outbreaks, such as in Malaysia, required the culling of over one million pigs to control transmission. However, the epidemiology of NiV among animal hosts, including pigs, horses, and bats, remains incompletely understood. NiV infection primarily affects the respiratory and nervous systems, causing severe pneumonia, vasculitis, and meningitis, while encephalitis may be mild or infrequent in some cases. This systematic review summarizes current evidence on NiV mutational variation, pathogenesis, treatment strategies, and vaccine development up to 2022. Data were collected from major databases, including PubMed, PMC, and Cochrane Library. Due to limited therapeutic options, NiV management relies mainly on supportive care, as no approved vaccines or specific antiviral treatments are available for humans or livestock. Preventive strategies focus on reducing zoonotic transmission, particularly by minimizing contact between livestock and bat-contaminated food sources, and improving farm management practices. Early detection and continuous surveillance of high-risk populations and animal reservoirs are essential for outbreak control. Current vaccine research targets viral antigens using subunit and vector-based approaches. Overall, further studies are urgently needed to develop effective vaccines and antiviral therapies for NiV infection.